Comparative study on the dye sensitized solar cell performance of solution processed ZnO - Jana, Arpita; Das, Partha Pratim; Agarkar, Shruti A.; Devi, P. Sujatha (Solar Energy, 2014)
We have monitored the performance of the dye-sensitized solar cells (DSSC) using solution processed ZnO having different shapes and aspect ratios. The aspect ratio and surface area of the ZnO structures have been regulated by carefully controlling the precursor concentration and reaction conditions. The shape of the synthesized structures has been varied from larger rods to smaller rods to hexagonal prisms. The synthesized hexagonal prism shaped ZnO with an aspect ratio of around one exhibited the highest surface area of 42 m(2)/g. The ZnO rods with higher aspect ratios of 5 and 16 exhibited lower surface areas of 22 and 2 m(2)/g, respectively. The dye sensitized solar cells constructed using the as-prepared ZnO structures and N719 dye molecules, exhibited efficiencies that varied as a function of surface area of the samples, with ZnO hexagonal prism exhibiting a maximum efficiency of around 1.38 +/- 0.01%. The results indicated a direct correlation between the surface area of the ZnO structures and the energy conversion efficiency. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: DSSC; Photoanode; surface area; ZnO